Perayaan Hari Besar Muhammadiyah dan Nadhlatul Ulama - Anisha Nurul Fatimah; Muh. Nur Rochim Maksum (Jurnal Budi Pekerti Agama Islam, 2024)
This study analyzes the differences in views between Muhammadiyah and Nahdlatul Ulama (NU) in celebrating Islamic holidays, with a focus on determining the beginning of the month of Qomariyah, celebrating the Prophet's birthday and tahlilan events in Indonesia. Muhammadiyah adopts a modernist approach with a focus on contextual understanding of religion, while NU maintains a traditional approach that emphasizes aspects of local culture and tradition. This study describes the values ​​of religious moderation that are highlighted within Nahdlatul Ulama. Since its founding, Hadratussyaikh K.H. Hashim Asy'ari initiated the concept of moderate Islam in Indonesia which was then continued by the next generation of NU, including K.H. Abdurrahman Wahid. The research method used in this research is a qualitative descriptive approach by conducting document analysis and literature study. The results of the research explain the differences in celebration practices and how each understands how to celebrate Islamic holidays.